2020
DOI: 10.1002/ijfe.2268
|View full text |Cite
|
Sign up to set email alerts
|

Do female managers perform better? Evidence from Italian manufacturing firms

Abstract: The aim of the paper is to test whether the presence of females on boards of directors influences firms productivity. The analysis is conducted on a large sample of Italian manufacturing firms extracted from the Analisi Informatizzata delle Aziende database for the years 2004 and 2012. Our results show that firm productivity is positively influenced by the presence of women managers in both post and pre-crisis periods, revealing that peculiar features of female human capital matter in running manufacturing fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Finally, it is worthwhile to mention that the results revealed that resilience was higher in females. The findings support Castiglione et al. (2022) who propounded that the presence of female managers positively influenced the firm’s productivity during pre- and post-crisis periods.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, it is worthwhile to mention that the results revealed that resilience was higher in females. The findings support Castiglione et al. (2022) who propounded that the presence of female managers positively influenced the firm’s productivity during pre- and post-crisis periods.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, it is worthwhile to mention that the results revealed that resilience was higher in females. The findings support Castiglione et al (2022) who propounded that the presence of female managers positively influenced the firm's productivity during pre-and post-crisis periods. Similarly, the findings are in line with Vasili c et al (2020) and Cosentino and Paoloni (2021) who showed that female managers contribute significantly toward enhancing the resilience capacity of companies.…”
Section: Discussionsupporting
confidence: 78%
“…Our results show that female managers significantly contribute to the ability of companies to overcome the crisis (Castiglione et al 2020;Vasilić et al 2020).…”
Section: Discussionmentioning
confidence: 60%
“…The same evidence has emerged in the COVID-19 era (Sultan and Sultan 2020). Otherwise, Castiglione et al (2020) found that a firm's productivity is positively influenced by the presence of women managers in post-and pre-crisis periods, revealing that female human capital is essential to the management of manufacturing companies. Grandy et al (2020) show that structural inequality and the (in)visibility of women's entrepreneurship have been amplified during the COVID-19 pandemic.…”
Section: The Factors Influencing a Firm's Value During A Crisis: Relational Capital Other Intangibles And Female Capabilitiesmentioning
confidence: 58%
See 1 more Smart Citation